2020
DOI: 10.1177/0269881120916137
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine-induced changes in behaviour and DNA methylation in rats are influenced by inter-individual differences in spontaneous exploratory activity

Abstract: Background: Individual differences in behavioural traits influence susceptibility to addictive disorders. Drug addiction involves changes in gene expression, proposed to occur via DNA methylation (DNAm). Aims: To investigate DNAm changes in reward-related brain structures (nucleus accumbens (NAc), lateral habenula (LHb)) in response to cocaine exposure in rats differing in spontaneous exploratory activity. Methods: Rats were observed in the exploration box and categorised as high- (HE) or low explorers (LE). R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…Addiction has been shown to be an altered DNA methylation signature in animal models, leading to changes in neuronal and brain activity following acute and chronic drug exposure [ 20 , 31 ]. Evidence from mammalian studies suggests that chronic cocaine administration interferes with DNA methylation dynamics and that gene expression in the brain may alter vulnerability to drug abuse [ 32 , 33 ]. However, cocaine-induced epigenetic modification of DNA methylation and cross-talk with mtDNA-mediated impairment in astrocytes is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Addiction has been shown to be an altered DNA methylation signature in animal models, leading to changes in neuronal and brain activity following acute and chronic drug exposure [ 20 , 31 ]. Evidence from mammalian studies suggests that chronic cocaine administration interferes with DNA methylation dynamics and that gene expression in the brain may alter vulnerability to drug abuse [ 32 , 33 ]. However, cocaine-induced epigenetic modification of DNA methylation and cross-talk with mtDNA-mediated impairment in astrocytes is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies based on blood cells have found that individuals who consume drugs show epigenetic changes that appear to relate to the frequency of use in a dose dependent man ner 113 . However, drug independent changes in addiction vulner ability triggered by adverse childhood experiences or other environ mental factors might have also contributed to the epigenetic modifi cations reported in individuals with SUDs 120 .…”
Section: Genetics and Epigeneticsmentioning
confidence: 99%
“…As drug exposure itself has been known to induce time-dependent DNA epigenetic changes in brain reward regions, the drug intake differences over time may therefore have contributed to differential methylation in the susceptible animals (Massart et al, 2015;Brown and Feng, 2017;Ploense et al, 2018;Sakharkar et al, 2019). However, a recent study (Vaher et al, 2020) provided evidence of drug dose-independent DNA epigenetic changes in addiction vulnerability. This was demonstrated in rats that were pre-screened for differences in exploratory behavior in a familiar environment [i.e., high and low explorers (Mällo et al, 2007)]; a behavioral phenotype that is similar to novelty-seeking and is concomitant with differential responding to substances of abuse (Alttoa et al, 2007).…”
Section: Dna Modifications and Addiction Susceptibilitymentioning
confidence: 99%
“…This was demonstrated in rats that were pre-screened for differences in exploratory behavior in a familiar environment [i.e., high and low explorers (Mällo et al, 2007)]; a behavioral phenotype that is similar to novelty-seeking and is concomitant with differential responding to substances of abuse (Alttoa et al, 2007). Cocaine intraperitoneal injections administered passively by an experimenter (i.e., each animal received identical drug doses) differentially regulated the expression of Dnmt3b and Tet3 in the NAc of high-and lowexploring rats, leading to phenotype-specific DNA methylation signatures at genes implicated in addiction (Vaher et al, 2020). Furthermore, these differences were only present after cocaine exposure, demonstrating that DNA epigenetic changes associated with addiction behavioral phenotypes may be drug dose independent.…”
Section: Dna Modifications and Addiction Susceptibilitymentioning
confidence: 99%